PENGARUH USIA TERHADAP PERSEPSI MASYARAKAT ATAS PERAN APOTEKER DALAM PELAYANAN SWAMEDIKASI - Koa, Oktaviana; Soegiantoro, Didiek Hardiyanto; Yuhara, Novena Adi (Jurnal Kesehatan Ilmiah Aufa Royhan, 2025)
Community pharmacists have an important role in public health services, especially in self-medication services, namely the use of drugs without a doctor's prescription to treat minor complaints, although public perception of the role of pharmacists can differ between regions; the purpose of this study was to see the extent of the influence of Indonesian public perception on the role of community pharmacists in self-medication service practices using quantitative methods with a cross-sectional design through the distribution of online questionnaires covering six variables: General Awareness (GA), Effectiveness (EFF), Collaboration (COLL), Barriers (BARR), Trustworthiness (TRUST), and Self-medication Services, where the validity test with KMO and Bartlett's Test and PCA factor analysis showed a KMO value > 0.771 which met the construct feasibility requirements, while Cronbach's Alpha reliability > 0.743 indicated very good internal consistency; Chi-Square analysis for the influence of age and Pearson correlation between variables yielded a significance value > 0.05, meaning there was no significant relationship between age and respondents' perceptions, indicating a consistent relationship between constructs, with the highest correlation between self-medication service and barriers (r = 0.780), indicating the higher the perceived barriers, the stronger the relationship with self-medication services. The government and pharmacists are intensifying education to reduce barriers, pharmacists are strengthening collaboration and trust through personalized consultations, developing mobile drug consultation applications, and further research in specific areas to explore other factors such as education.